KESADARAN MENABUNG SEJAK DINI BAGI PELAJAR SMAN 1 LINTAU BUO TANAH DATAR SUMATERA BARAT - Atikah Mahdiyyah (2022)
Awareness of saving money from an early age, should have become a pattern of life for society, especially for high school students because at that productive age, they have to prepare financial needs for the life to come, but with the existence of various factors, one of which is free trade so that people live with a pattern of life. consumptive, therefore it is necessary to know how awareness, interest, and financial considerations are applied. The object of this research is the students of SMAN 1 Lintau Buo West Sumatra. This study uses primary data from questionnaires distributed to 40 students. The sampling technique used is purposive sampling. The results obtained can be concluded that, the interest and awareness of saving from an early age in respondents is quite good but of course there must be more efforts to improve this, the factors that encourage respondents to save also vary, from the amount of pocket money received, parents' occupations, people's income. elders etc., it is hoped that the next writer will be able to enrich the questions so that they can get more in-depth information. The related parties also carry out interesting literacy activities for local students